AUTOMATION SYSTEM BASED ON ARDUINO ( Case Study in AQUAPONIC TOURISM VILLAGE ) - Apito Wahyu Harsoyo; Setiyo Adi Nugroho (Journal of Technology Informatics and Engineering, 2023)
Problems often faced by Perum Kandri residents regarding Aquaponics during the dry and rainy seasons. Residents still use tarpaulins to cover aquaponics manually, and feeding is still done manually. Aquaponic maintenance tools can be a solution for residents, to detect temperature and raindrops automatically, the author uses a DHT temperature sensor, raindrop sensor, RTC, mini servo, continuous servo and Arduino Uno R3 to design this maintenance tool. The tool that the author created can handle hot temperatures and during the rainy season, as well as feeding fish automatically , thereby reducing the possibility of the danger of death to vegetables and fish . The writer's tool can also close the roof automatically if it rains or hot during the day.